Arsenate content, and arsenate/phosphate and arsenate/sulphate competitive adsorption in soils from Minas Gerais, Brazil Teor de arsênio e adsorção competitiva arsênio/fosfato e arsênio/sulfato em solos de Minas Gerais, Brasil - Guilherme L.R.G. (2013)
The high toxicity of arsenic to humans and animals creates the need to study the chemical behavior of arsenate in soils that can help in the mitigation of areas contaminated with arsenic. This work aimed to evaluate the total content and adsorption in the absence and presence of phosphate and sulfate anions in six different soil classes in the state of Minas Gerais, Brazil. Soils aim of this study are: Fluvic Neosol (RU), Haplic Gleysol (GX), Melanic Gleysol (GM) and Typical Distrophic Red Latosol (LVd) collected in Lavras, MG; Quartzenic Neosol (RQ) collected in Itutinga, MG, and Typical Distrophic Yellow Latosol (Lad) collected in Rosário, MG. Soil samples were dried, ground and sieved through a sieve of 2mm for the test run of adsorption and sieved through a sieve with a mesh of plastic 1.5mm for the As determination. The As content was determined by the method 3051A. The rate 1500μmolL-1As, 1500μmol L-1 As + 1500μmol L-1 P, 1500μmol L1 As + 750μmol L-1 As were used to evaluate As adsorption, soil solution rate of 1:100, pH 5,5 and ionic force of 15mmol.L-1. The mean As content in the six soils was between 0,14 and 9,3mgkg-1. The adsorpted percentage of As in absence of other anions followed the sequence GM>LVd=RU=LAd=GX=RQ. Phosphate and sulphate addition reduced the percentage of adsorpted arsenic, consequently there was an increase of disponible arsenic in the soil solution.